IT Required Skills in Accounting: A Comparative Analysis Across European Labour Markets - Sinziana-Maria Rindasu (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Research Question - The research proposition is to identify the information technology (IT) skills required from accounting professionals by the labour market from European emerging and developed economies and analyse whether there are differences between the requirements, depending on the type of economy. Motivation - The wide adoption of several emerging technologies across various domains of activity is a widely debated topic. However, regardless of its popularity, little research focused on comparing the expectation of the professional bodies and the current labour market expectations in terms of the IT skills accountants should demonstrate. Idea - This study aims to analyse if there is any gap between the expectations formulated by accounting professional bodies and the labour market's requirements in European countries regarding the IT skills accountants should demonstrate. Data - The dataset selected for this study consisted of 1000 accounting job advertisements, collected between two periods: September 2017 - July 2018 and January - February 2021. Tools - A cross-sectional study, including a content analysis and statistical analyses, was conducted to analyse the dataset collected. Findings - The results illustrate the European labour market's current expectations regarding the IT skills accountants should demonstrate. The statistical analyses conducted highlight an association between the skills asked by emerging and developed European based companies. Contributions - This paper provides a glimpse regarding the European labour market's expectations in terms of IT skills requested from accounting professionals, thus being a reference for the European professional bodies and academia.
Keywords: M15; M41; M54; O33; 650; accounting education; information systems; IT skills; digitalised accounting; accounting graduates